Conflitos socioambientais e mudanças climáticas sob o olhar das juventudes camponesas de Poconé - Mato Grosso - Bertoncello, Jucieli (2018)
Through this research we seek to understand the perceptions of peasant youth about socioenvironmental conflicts and climatic changes existing in the traditional community of ‘Nossa Senhora de Lurdes’ (known as ‘Zé Alves’) and in the Remaining ‘Quilombo Laranjal’ community, both located in the municipality of Poconé, Mato Grosso, Brazil, known as "Cerrado do Pantanal". We point out that the conflicts are due to unequal disputes between vulnerable social groups that have their culture, identity and territory threatened by dominant groups, especially agribusiness, that transforms natural assets into resources within economic logic, based on productivism and over consumption. In the Cerrado of the Pantanal (wetland), which is the locus of this research, the deforestation carried out in favor of monoculture, together with cattle ranching and mining has led to conflicts between the owners of these large enterprises and the populations that survive basically from extractivism and peasant family farming. These economic activities are also responsible for the increase of disasters related to climate change, which disproportionately reach different groups living in these territories due to social and economic vulnerability. In this context, the present research is enrolled in the project entitled Environmental Education and Climate Justice Network (REAJA) coordinated by the Research Group on Environmental Education, Communication and Art (GPEA), being a multidisciplinary network that seeks to understand climatic phenomena and disasters that affect different social groups in a contradictory, unequal and unfair way. The investigative proposition is based on the qualitative method, having as methodological tactics the Social Map that seeks to highlight invisible groups and social-environmental injustices that turn into conflicts while resistance and mobilization are established in the territories. In order to obtain the information of this research, we carried out seven fieldwork, two mapping seminars with the communities in the Cerrado of the Pantanal, twelve semi-structured interviews with the youths of the communities Zé Alves and Laranjal, as well as secondary sources (reports, articles and censuses) on the communities surveyed. Through the mapping were registered six causes of conflicts: land dispute, deforestation, burning, mining, water dispute and use of pesticides that occur mainly between quilombolas (african descendants) and farmers; settlers and farmers; traditional people and farmers; and between quilombolas and quilombolas. The narratives of the youths showed five causes, disregarding only the existence of mining. Thus, by giving visibility to the quilombolas, traditional and settled people in this territory about the socioenvironmental conflicts and climate change through the eyes of youth represents more than a tactic of democratization of information, but the search for a fairer and more democratic society.